2018
DOI: 10.1080/15419061.2018.1493107
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanofiber coated with l-arginine via electrospinning technique: a novel nanomatrix to counter oxidative stress under crosstalk of co-cultured fibroblasts and satellite cells

Abstract: The objective of this study was to synthesize and characterize novel polyurethane (PU)-nanofiber coated with l-arginine by electrospinning technique. This study determined whether l-arginine conjugated with PU-nanofiber could stimulate cell proliferation and prevent HO-induced cell death in satellite cells co-cultured with fibroblasts isolated from Hanwoo (Korean native cattle). Our results showed that l-arginine conjugated with PU nanofiber could reduce cytotoxicity of co-cultured satellite cells. Protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Polymers such as polyvinyl alcohol (PVA) [30,79], PCL [80] and PEO [44,76,81,82] are required to achieve a bead-free morphology and overcome brittleness of the material (Table 1). Only a limited number of studies have, therefore, focused on applying soy-based nanofibers for wound healing [44,[81][82][83], even though soy protein contains reactive amino acid residues such as arginine, glycine, aspartic acid and glutamine that facilitate wound healing through cell attachment and proliferation [83][84][85][86]. Higher cell proliferation in vitro has been demonstrated in electrospun soy protein in comparison to a solvent cast film, which has been attributed to the porous nanofibrous matrix that allows better nutrient access [83].…”
Section: Soy Proteinmentioning
confidence: 99%
“…Polymers such as polyvinyl alcohol (PVA) [30,79], PCL [80] and PEO [44,76,81,82] are required to achieve a bead-free morphology and overcome brittleness of the material (Table 1). Only a limited number of studies have, therefore, focused on applying soy-based nanofibers for wound healing [44,[81][82][83], even though soy protein contains reactive amino acid residues such as arginine, glycine, aspartic acid and glutamine that facilitate wound healing through cell attachment and proliferation [83][84][85][86]. Higher cell proliferation in vitro has been demonstrated in electrospun soy protein in comparison to a solvent cast film, which has been attributed to the porous nanofibrous matrix that allows better nutrient access [83].…”
Section: Soy Proteinmentioning
confidence: 99%
“…However, despite the fact that arginine plays an important role in the process of tissue regeneration, few examples of its use in the modification of polymer scaffolds exist. It has been found that electrospun polyurethane modified with arginine counters oxidative stress in vitro, thus increasing its utility as a wound dressing [15]. Arginine has been used to modify PCL by electrospinning in the formation of scaffolds [16], and it was found that increasing the arginine concentration in the spinning solution decreased the diameter of the formed fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Modifying nanofibers with L-arginine has been dealt with in only a small number of papers. Subramaniyan et al coated polyurethane nanofibers with L-arginine for biological in vitro testing [20]. Other authors have modified the surface of a lignin or cellulose nanofiber gel with L-arginine for wound healing [21,22].…”
Section: Introductionmentioning
confidence: 99%